1995
DOI: 10.1016/0009-2614(95)00206-j
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and observation of ring and chain isomers in Sn− i ons

Abstract: Experimental and theoretical studies have been performed on singly charged anions of sulphur clusters S,~ up to n = 9. Density functional calculations with simulated annealing predict the existence of two general classes of structure comprising rings and chains, respectively, with markedly different vertical detachment energies (VDE) for transitions to states of the neutral clusters. VDE and vibration frequencies obtained from photoelectron detachment measurements using a pulsed arc cluster ion source (PACIS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…4b), the most stable form of sulfide radicals in nature 41 , other kinds of polysulfide radicals such as S 4˙-40,42 or even longer-chain radicals may also be present concurrently in the transient states via the cleavage of the polysulfide rings or chains under the electrical field, considering the highly insulating nature of sulfur. However, the structural stability of other longer-chain radicals is poor and it is likely that they immediately transform to the more stable 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 forms, e.g., S 3˙-and S 2˙-, that have been identified by ex situ EPR experiments 43,44 . In fact, a recent work using in situ XAS measurements reported the existence of S 3˙-radicals generated during the electrochemical reactions, further confirming the critical effects of sulfur radicals in the system 45 .…”
Section: Resultsmentioning
confidence: 94%
“…4b), the most stable form of sulfide radicals in nature 41 , other kinds of polysulfide radicals such as S 4˙-40,42 or even longer-chain radicals may also be present concurrently in the transient states via the cleavage of the polysulfide rings or chains under the electrical field, considering the highly insulating nature of sulfur. However, the structural stability of other longer-chain radicals is poor and it is likely that they immediately transform to the more stable 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 forms, e.g., S 3˙-and S 2˙-, that have been identified by ex situ EPR experiments 43,44 . In fact, a recent work using in situ XAS measurements reported the existence of S 3˙-radicals generated during the electrochemical reactions, further confirming the critical effects of sulfur radicals in the system 45 .…”
Section: Resultsmentioning
confidence: 94%
“…15,46 In wet chemistry, the sulfur species in the red solution prepared from sulfur and Na 2 S 4 in DMF, HMP (hexamethylphosphoric triamide) or acetone was thought to be the red S 4 ¹ anion. However, no convincing proof for it has been obtained from spectroscopic studies.…”
Section: Smentioning
confidence: 99%
“…Zakrzewski 16b and Ganteför 15,46 groups have optimized the geometry of the S 4 ¹ anion using the HF/6-31+G* and a combination of density functional calculation with molecular dynamics (MD/DF), respectively: both the groups have suggested that a planar C 2v species is the most stable isomer. However, Morokuma et al have mentioned that the free S 4 ¹ anion has the C 2h isomer as the most favorable structure using QCISD(T)/MC-311G(2d).…”
Section: Smentioning
confidence: 99%
“…as metal, sulfur, and carbon clusters [15][16][17][18][19][20]. The pulsed arc discharge may normally produce relatively small clusters (n ∼ 30).…”
Section: Introductionmentioning
confidence: 99%